Assessment of Knowledge and Dietary Misconceptions among Diabetic Patients - Akbar, Naila; Aqeel, Talieha; Haq, Noman-Ul-; Naseem, Aqeel; Dhingra, Sameer (Journal of Pharmacy Practice and Community Medicine)
Background: Diabetes mellitus (DM) is a major health problem globally and so are misconceptions. Misconceptions can lead to poor glycemic control among diabetic patients and hence may results in complications and therefore increased incidence of morbidity and mortality. Objective: Assessment of knowledge and dietary misconceptions among diabetic patients. Methodology: A cross-sectional prospective study was conducted among diabetic patients for a period of 6 months, using a validated questionnaire. Patients were contacted while attending to a health care facility in Quetta, Pakistan. A self-administered questionnaire was introduced among participants. Assistance was provided to those who could not read or understand the questionnaire. The questionnaire was designed in English and then translated in to Urdu by a language expert. The data were coded and entered to statistical package for social sciences (SPSS) version 20. The responses to the questionnaire were analyzed by performing descriptive and inferential statistics. Results: Study showed that almost 83% of diabetic subjects believed that “in diabetes sugar cannot be used at any cost”, while 68% believed that special diabetic food is used in diabetes; almost 66% patients admitted that they can suffer from other diseases and infections due to diabetes. Misconceptions were more common among uneducated and low income people. Conclusion: The prevalence of misconceptions about Diabetes is high among uneducated and low income people.
Keywords: Diabetes Mellitus; Knowledge; Misconceptions; Myths; Treatment; Pakistan